PENGARUH INIFLASI DAN DANA PIHAK KETIGA TERHADAP PEMBIAYAAN (BUS DAN UUS DI INDONESIA TAHUN 2003 – 2015) - Matondang, Zulaika (Institut Agama Islam Negeri Padngsidimpuan, 2016)
Abstract The development of Islamic Banks and Sharia Business Unit has increased from year to year, so does the amount of funding has increased from year to year. There are several factors that affect the financing of which is iniflasi and third party funds. increase in third party funds followed by an increase in financing, but iniflasi tend to fluctuate from year to year. So the purpose of this study was to measure the effect of iniflasi and third party funds to finance BUS and UUS in Indonesia period 2003 - 2015. The research showed that iniflasi have an impact on financing BUS and UUS evidenced t t table (4.152 2 , 00 856), and third party funds also affects the financing BUS and UUS which is evidenced by the t t table (173.294 2.00856). And simultaneously between iniflasi and third party funds to finance BUS and UUS evidenced by F count F table (16098.426 4.03431) with the influence iniflasi and DPK to financing BUS and UUS in Indonesia amounted to 99.8 per cent while the rest 0.2 percent are influenced by other factors outside the study variables.Keywords : Inflation, DPK, Financing.